Institutional mechanisms for promoting accountability in the Philippine Civil Service - Yangco, Mario D. (1991)
In the Philippine Civil Service, major institutional mechanisms for enforcing accountability in the civil service are in place. Amongst these are enforcement of a code of conduct and ethical standards, personnel inspection and audit, monitoring agency performance appraisal, administrative discipline, the fast track provincialization programme of the Civil Service Commission Service and others.
Keywords: Government accountability -- Philippines; Finance, Public -- Accounting